Education and education with values in the face of contemporary challenges - Beata Rola; Jarosław Rola (Studia z Teorii Wychowania)
The current reality, with its multidimensionality and challenges related to the increasingly experienced diversity, affects the sense of stability and security among children and adolescents. Assuming that school is a place where every student has a chance to develop adaptive skills, it is this environment that should provide high-quality role models as well as a focus on stable values that will build social sensitivity and mental strength of students. In this text, we present practical solutions on how to explore the essence of values and at the same time put them into practice. We encourage educators, teachers and caregivers to consider education with values as a way to develop in students a certain philosophy of life that supports their maturation, full development and decisions, and thus fosters inclusion in the community with respect, trust and a sense of meaning. The material contains a theoretical part referring to the assumptions of positive psychology and several ideas, such as exercises on implementing key values.